Dynamics of special endurance of athletes aged 13-15 years under the influence of the program of the Cossack duel - Andrij Plokhikh; Gennadij Ogar (Pedagogy of Health)
Background and Study Aim. National sports are gradually spreading around the world and becoming international. One of such sports is the Cossack duel - a national martial art in Ukraine. In addition to the purely sports component, this sport has national traditions of educating healthy youth. The purpose of the study is to identify the impact of the Cossack duel program on the special endurance of athletes aged 13-15 year.